2006
DOI: 10.1128/aem.00938-06
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization of Chitinase-Deficient Bacillus licheniformis Strains Capable of Deproteinization of Shrimp Shell Waste To Obtain Highly Viscous Chitin

Abstract: Proteolytic but chitinase-deficient microbial cultures were isolated from shrimp shell waste and characterized. The most efficient isolate was found to be a mixed culture consisting of two Bacillus licheniformis strains, which were first determined microscopically and physiologically. Molecular characterization was carried out by sequencing the 16S rRNA gene of both strains. According to the residual protein and ash content, the chitin obtained by fermentation of such a mixed culture was found to be comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 30 publications
1
52
0
6
Order By: Relevance
“…Shanmugaiah et al (2008) reported that among the 39 chitinolytic bacteria which were isolated from rice rhizosphere, only 11 isolates produced zone of clearance over 0.5 cm on chitin colloidal agar. Chitinase production was reported in different species of Bacillus such as B. amyloliquefaciens (Wang et al, 2002), B. cereus (Huang et al, 2005), B. circulans (Chen et al, 2004), B. licheniformis (Waldeck et al, 2006), B. megaterium (Donderski and Brzezinska, 2005), B. stearothermophilus (Sakai et al, 1994), B. subtilis (Wang et al, 2006), B. thuringiensis sub sp. aizawai (De la Vega et al, 2006), B. thuringiensis sub sp.…”
Section: Discussionmentioning
confidence: 99%
“…Shanmugaiah et al (2008) reported that among the 39 chitinolytic bacteria which were isolated from rice rhizosphere, only 11 isolates produced zone of clearance over 0.5 cm on chitin colloidal agar. Chitinase production was reported in different species of Bacillus such as B. amyloliquefaciens (Wang et al, 2002), B. cereus (Huang et al, 2005), B. circulans (Chen et al, 2004), B. licheniformis (Waldeck et al, 2006), B. megaterium (Donderski and Brzezinska, 2005), B. stearothermophilus (Sakai et al, 1994), B. subtilis (Wang et al, 2006), B. thuringiensis sub sp. aizawai (De la Vega et al, 2006), B. thuringiensis sub sp.…”
Section: Discussionmentioning
confidence: 99%
“…For a comparison of the mutants generated with a strain carrying the reconstituted chiA gene (the formerly published frameshift mutation in chiA of F11 [43], yielding a premature translational stop), the defective chiA sequence from B. licheniformis F11 was exchanged for that of the intact chiA gene of B. licheniformis DSM13 (see Materials and Methods). The relevant genotypes of the respective strains and the deviations from wild-type strain F11 are depicted in Fig.…”
Section: Generation Of Mutantsmentioning
confidence: 99%
“…B. licheniformis DSM13 possesses an operon with two chitinase genes, chiB and chiA, which possibly hampers the recovery of high-molecular-mass chitin due to degradation. B. lichenifor-mis strain F11 has a frameshift mutation in the chitinase A gene (chiA); it was efficiently used in shrimp shell protein hydrolysis, at the same time leaving the chitin largely unaffected (43). However, the other chitinase-encoding gene (chiB) localized immediately upstream of chiA as part of the operon may still have a negative impact on chitin recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The modified agar diffusion method was used to visualize SCChi-1 chitinase activity (18,19). First, the colloidal chitin, glycol chitin, glycol chitosan, and soluble chitosan plates were prepared.…”
Section: Substrate Specificity Of Scchi-1mentioning
confidence: 99%